Investigating the Effect of Job Motivation on Employee Work Quality at Honda Workshop: The Mediating Role of Dominion Power - Damanik, Sri Winda Hardiyanti; Sinurat, Mangasi; Siahaan, Rumiris; Purba, Rakhmawati; Jayadi, Usman; Ilham, Rico Nur; Riinawati, Riinawati (International Journal of Business, Economics & Financial Studies, 2024)
Performance is vital for organizational success, and employee work quality is essential. A decline in individual or group performance can significantly affect a company's effectiveness. This study, conducted at the Honda Sei Rampah Dealer beginning in July 2020, used quantitative data analysis to investigate the independent variables of dominion power image and employee work quality, with dominion power as the dependent variable. The study involved 45 employees (43 males and 2 females, aged 18–29, both single and married). Validity testing was performed using SPSS version 17.00, based on the calculated r values. Partial hypothesis testing assesses the impact of each independent variable on the dependent variable. The findings indicated a significant relationship between job motivation and employee work quality and that dominion power had a notable effect on employee quality. Future research should explore dominion power among employees, especially their resilience in challenging work environments, through encouragement initiatives. Examining colleagues’ relationships and implementing stricter regulations to enhance compliance and obedience may also be beneficial. To better understand the complexities of dominion power and its impact on organizations, future studies should incorporate more variables that could lead to improved organizational performance and effectiveness.